Emotional Gratification as a Predictor of Internet and Gaming Disorder Tendency in Adolescent Roblox Users - Nadiya Andromeda; Tirta Danayaksa (CV Edujavare Publishing, 2026)
This study aimed to examine the effect of Emotional Gratification on Internet Gaming Disorder (IGD) among adolescent Roblox users in Malang City. A quantitative predictive research design was employed. The sample consisted of 96 adolescents aged 11–18 years who actively used Roblox and were selected through snowball sampling. Data were collected using the Emotional Gratification Scale, which measures enjoyment, escapism, social interaction, and achievement, and the Internet Gaming Disorder Scale based on DSM-5 criteria. The data were analyzed using simple linear regression. The results indicated that the data were normally distributed and that the relationship between variables was linear. Regression analysis revealed that Emotional Gratification had a positive and significant effect on Internet Gaming Disorder (β = 0.547; t = 7.10; p < .001). The coefficient of determination (R² = 0.349) indicated that Emotional Gratification accounted for 34.9% of the variance in Internet Gaming Disorder. These findings suggest that higher emotional gratification obtained through Roblox is associated with a greater tendency toward Internet Gaming Disorder among adolescents.